2016
DOI: 10.1038/mp.2016.166
|View full text |Cite
|
Sign up to set email alerts
|

The birth, death and resurrection of avoidance: a reconceptualization of a troubled paradigm

Abstract: Research on avoidance conditioning began in the late 1930s as a way to use laboratory experiments to better understand uncontrollable fear and anxiety. Avoidance was initially conceived of as a two-factor learning process in which fear is initially acquired through Pavlovian aversive conditioning (so-called fear conditioning), and then behaviors that reduce the fear aroused by the Pavlovian conditioned stimulus are reinforced through instrumental conditioning. Over the years, criticisms of both the avoidance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
263
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(281 citation statements)
references
References 197 publications
7
263
0
11
Order By: Relevance
“…Thus, PL may be in direct communication with BLA to express avoidance memories, similar to Pavlovian fear conditioning (Cho et al 2013). Projections from basal amygdala to VS have been shown to mediate active avoidance (Ramirez et al 2015), supporting the idea that BLA is a central hub for defensive reactions (LeDoux et al 2017). What then might be the function of PL inputs to BLA?…”
Section: Discussionmentioning
confidence: 64%
“…Thus, PL may be in direct communication with BLA to express avoidance memories, similar to Pavlovian fear conditioning (Cho et al 2013). Projections from basal amygdala to VS have been shown to mediate active avoidance (Ramirez et al 2015), supporting the idea that BLA is a central hub for defensive reactions (LeDoux et al 2017). What then might be the function of PL inputs to BLA?…”
Section: Discussionmentioning
confidence: 64%
“…The underlying psychological nature of avoidance behavior is not very well understood (LeDoux et al, 2016). While this form of learning is sensitive to elements of negative reinforcement such as response feedback and shock omission (Kamin, 1956), other nonreinforcement based accounts have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely because control subjects in this study also showed very little freezing to the CS, as is commonly observed in aversive PIT (Campese et al, 2013). Many published reports find that over the course of avoidance training, freezing CRs are attenuated as avoidance behavior emerges (LeDoux et al, 2016). This is true when avoidance training includes an explicit signal (Cain and LeDoux, 2007; Choi et al, 2010; Moscarello and LeDoux, 2013) as well as in unsignaled avoidance learning paradigms such as that used in the current paper where freezing to the context is reduced over training (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A growing literature describes the brain circuits involved in determining whether an animal will respond to a threat-associated stimulus with passive avoidance (freezing; see also the dissociative subtype of PTSD, Box 2) or more active avoidance strategies (such as running towards a safe chamber) 59 . Both strategies can be maladaptive if used excessively or in a fashion in which the individual has no control; however, there is evidence to suggest that active avoidance strategies can dampen responses to subsequent stressors 60 .…”
Section: Avoidancementioning
confidence: 99%